Optimisation of surface finishes for oriented strand board in order to increase its moisture resistance - Kratochvílová, Erika; Patloka, Jiří; Šlanhof, Jiří (IOP Publishing, 2019)
The purpose of the research is the optimisation of surface finishes for application to oriented strand board (OSB) in order to increase its moisture resistance. The aim of the research is to compare test specimens with different types of coating, spray, primer and waterproofing under predefined conditions and different forms of moisture exposure. The paper contains a definition of the basic material, test specimens and test methods, and covers 8 different types of surface finish materials selected for application to the test specimens. The results include graphs showing growth in humidity over time, specifically graphs showing the causal relationship between increases in weight and moisture absorption, as well as graphs depicting swelling in thickness. The results are also discussed. In the conclusion the results are evaluated and an outline of the next steps to take with regard to further research is formulated. The results are of benefit to all subjects concerned with wooden structures in which OSB is used, both at the design stage and at the stage of the preparation and execution of construction with respect to unpredictable weather conditions that can irreparably damage unprotected structures. In addition, these are results which are important for the operation of buildings during which a suitable surface finish can alleviate the consequences of later accidents and defects. They may also be beneficial during the construction of buildings from structural insulated panels who's facing most often consists of OSB. Construction periods tend to be adversely affected by changes in the weather. The application of suitable surface finishes to OSB immediately during the prefabrication stage could eliminate this issue.

The purpose of the research is the optimisation of surface finishes for application to oriented strand board (OSB) in order to increase its moisture resistance. The aim of the research is to compare test specimens with different types of coating, spray, primer and waterproofing under predefined conditions and different forms of moisture exposure. The paper contains a definition of the basic material, test specimens and test methods, and covers 8 different types of surface finish materials selected for application to the test specimens. The results include graphs showing growth in humidity over time, specifically graphs showing the causal relationship between increases in weight and moisture absorption, as well as graphs depicting swelling in thickness. The results are also discussed. In the conclusion the results are evaluated and an outline of the next steps to take with regard to further research is formulated. The results are of benefit to all subjects concerned with wooden structures in which OSB is used, both at the design stage and at the stage of the preparation and execution of construction with respect to unpredictable weather conditions that can irreparably damage unprotected structures. In addition, these are results which are important for the operation of buildings during which a suitable surface finish can alleviate the consequences of later accidents and defects. They may also be beneficial during the construction of buildings from structural insulated panels who's facing most often consists of OSB. Construction periods tend to be adversely affected by changes in the weather. The application of suitable surface finishes to OSB immediately during the prefabrication stage could eliminate this issue.
Optimisation of surface finishes for oriented strand board in order to increase its moisture resistance
Keywords: Moisture; Oriented Strandboard; Surface finish; Swelling; Moisture; Oriented Strandboard; Surface finish; Swelling